Estimasi Sumberdaya Pit 1 Blok Selatan dengan Metoda Silcular 5015-2019 Daerah Puruk Cahu Kalimantan Tengah - Asep Tri Herdianto,; Erwin Wijaya, Andy (ReTII, 2024)
Coal is one of the energy minerals found in Indonesia with significant potential, particularly in Kalimantan. The objective of this research is to calculate a more accurate estimate of reserves in the study area with a thickness range of 1-1.2 meters. The distribution of the seam generally follows a pattern from Northeast to Southwest with a moderate dip angle of 70-80 degrees. Based on SNI 5015-2011, the geological complexity of the study area falls into the â€œComplexâ€ category according to SNI 5015-2019 due to the steep inclination of the rock layers. The estimation of coal resources using the Circular Method, aided by software, yielded the following results: measured coal resources of 1,127,778.23 tons, indicated resources of 2,024,364.08 tons, and inferred resources of 2,948,000.06 tons.